Methods for Solving Environmental Problems in Livestock and Poultry Farming - A. Yu. Bryukhanov; E. V. Vasilev; E. V. Shalavina; R. A. Uvarov (Сельскохозяйственные машины и технологии)
In the Northwestern Federal District, the main agricultural source of environmental pollution is the disposal of organic waste (manure and litter), which accounts for a risk of 85 percent. The problem of ensuring environmental safety requires appropriate solutions based on modern intelligent machine technologies, means of monitoring and controlling technological processes of organic waste disposal. (Research purpose) To provide rationale for combined methods of solving environmental problems in animal and poultry farming. (Materials and methods) The authors studied the environmental impact of machine technologies used in livestock and poultry farming. The studies were carried out by assessing environmental risks and the sustainability of agroecosystems, applying methods and techniques for assessing the best available technologies, and studying the main prospects of developing intelligent digital technologies. (Results and discussion) The authors have identified the main methods of solving the environmental problems associated with large farm enterprises, including the calculation, design and system operation of the best available technologies for agricultural production. They have proposed a technical tool in the form of a bioreactor for the disposal of organic waste, capable of reducing manure and litter processing period in 60 times and providing automated flow and process control with online registration of production and environmental indicators. They have described an intelligent system for monitoring and utilizing organic waste, including a conceptual framework for establishing modular centers for deep processing. (Conclusions) The authors have proved that the implementation of modern methods for ensuring effective and environmentally safe agricultural production requires the establishing of experimental plot sites for complex research and demonstration of a “machine technology – monitoring – management” system. It has been proposed that a site of the VIM agrobiotechnological cluster should be established at a pilot livestock complex enterprise in the Leningrad Region. The authors have identified promising areas of research to ensure the transition of agricultural production to a new technological structure that implements the principles of Smart Farming to provide for the disposal of at least 510 million tons of agricultural organic waste a year.